If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 5x + 37 = x + 5 Reorder the terms: 37 + 5x = x + 5 Reorder the terms: 37 + 5x = 5 + x Solving 37 + 5x = 5 + x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-1x' to each side of the equation. 37 + 5x + -1x = 5 + x + -1x Combine like terms: 5x + -1x = 4x 37 + 4x = 5 + x + -1x Combine like terms: x + -1x = 0 37 + 4x = 5 + 0 37 + 4x = 5 Add '-37' to each side of the equation. 37 + -37 + 4x = 5 + -37 Combine like terms: 37 + -37 = 0 0 + 4x = 5 + -37 4x = 5 + -37 Combine like terms: 5 + -37 = -32 4x = -32 Divide each side by '4'. x = -8 Simplifying x = -8
| Z-5=60 | | 4(2c-1)-5=6c+5 | | (3/8)*(5/6)=x | | r+p+2=3r-4-3p | | 5h+60=8h | | -3x-20=x+12 | | X+89=4+6x | | -16v=7 | | 4x+38=3x | | 141=3(x+3)+9x | | 3/5x-11=37 | | -7x+5(4x+4)=-110 | | -7p-8+8=7 | | 6x^2+30x+48=0 | | 10+7b+8b-17= | | -3x+6(-3x-18)=-3 | | 85-9w=1+3w | | 3x-5+6=2x-3 | | 9-16x+10x-4y= | | -7x-7(5x-15)=-189 | | -17=-1-6k+8 | | 3x^2+6x+3y^2-9y-48=0 | | 3x+1+2x+12= | | 4f-12=3-f | | 39x-10-12=01 | | 7x-3(-x+3)=-119 | | 2x-5/12=9 | | g^2+2g-120=0 | | 89=5(1+8x)+2x | | A+4=3b | | 70+8n=3n | | 12x-x+2=30x |